A comprehensive evaluation of plasma metagenomics sequencing for the diagnosis of suspected infection in pediatric patients with hematologic diseases - Zhang, Shihai; Guo, Qiang; Gai, Wei; Guo, Yuxin; Zheng, Yafeng (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundAs a non-invasive technology, plasma cell-free DNA (cfDNA) next-generation sequencing (mNGS) has been widely used for clinical detection of a variety of infectious diseases. Infections are a major cause of poor prognosis in children with hematologic diseases. So far, there has been limited research on the use of plasma cfDNA mNGS in children with hematological disorders at high risk of infection.MethodsWe retrospectively analyzed the clinical data of 73 children with hematological disorders suspected of early infection admitted to Anhui Children’s Hospital between September 2023 and February 2024. The diagnostic performance and clinical implications of mNGS versus conventional microbiological testing (CMT) were evaluated.ResultsThe positive rate of mNGS was significantly higher than that of CMT (69.86% vs 31.51%, P < 0.001). When compared with the final clinical diagnosis, the sensitivity of mNGS was significantly higher than that of CMT (71.88% vs 35.94%, P < 0.001). There is a high degree of agreement between the positive results of the two assays (78.95%). A total of 46 pathogens were identified in children with hematologic diseases, of which 41 pathogens were detected by mNGS and only 12 pathogens were detected by CMT. In these patients, the most common bacteria detected were Klebsiella pneumoniae and Mycoplasma pneumoniae. Human betaherpesvirus 5 (CMV) was the most commonly detected virus. All fungi were detected only by mNGS. Overall, mNGS had a positive effect on the clinical treatment for 65.75% of patients in this study. Positive results are more likely to be obtained with mNGS when white blood cell counts, neutrophil counts, and lymphocyte counts are low.ConclusionsEarly plasma cfDNA mNGS improved the performance of pathogen detection in children with hematological diseases. Rapid identification of the pathogen followed by precise targeted antimicrobial therapy improves the prognosis of patients.